Pulse-Shape Control in an All Fiber Multi-Wavelength Doppler Lidar - Töws Albert; Lehmann Jan; Kurtz Alfred (EPJ Web of Conferences, 2016)
Pulse distortion during amplification in fiber amplifiers due to gain saturation and cross talk in a multi-wavelength Doppler lidar are discussed. We present a feedback control technique which is capable of adjusting any predefined pulse shape and show some examples of feedback controlled pulse shapes.